ASAS KURIKULUM PENDIDIKAN ISLAM : Studi Analisis Pemikiran Pendidikan Buya Syakur Yasin - romlah romlah; Nurullah Nurullah (Jurnal Pendidikan Educandum, 2024)
Buya Syakur is a charismatic scholar whose intelligence is very broad, and very relevant to the times, his direction of thinking which prepares and produces cadres to create a nation that is very precise and extraordinary, by cultivating and developing enthusiasm and synergizing with socio-cultural realities. The indication is that apart from students understanding religion, first they do not rule out social life. Based on taukhid, as the main basis for implementing the Islamic education curriculum (having a good relationship with God). The meaning of taukhid here is not only to acknowledge the oneness of God (divine unity), but also to be proven by real reality by acknowledging the relationship between humans and others (hablun min al-nas, anthropo-sociological aspects), and the relationship between humans and their natural environment. (hablun min al-'âlam, cosmological aspect). Second, the Islamic Education curriculum that was initiated by Buya Syakur is good morals. This is aimed at providing provisions for children with good morals and a clean soul. The third principle of the curriculum is lifelong learning. This means that God gives an appeal to humans to always remember and always learn throughout life. Don't be afraid to fail or give up. The hope of Buya Syakur's thinking is to make humans as themselves and their gods, so that they realize that as a noble being, they must have noble privileges as well, so that ultimately create a cadre of understanding of religious values, proven by behaving well, broad in thinking, logical in opinion and have a clean soul. Keywords: Basic Curriculum And Islamic Education